An adaptive test of stochastic monotonicity - Denis Chetverikov; Daniel Wilhelm; Dongwoo Kim (Centre for Microdata Methods and Practice (cemmap), 2018)
We propose a new nonparametric test of stochastic monotonicity which adapts to the unknown smoothness of the conditional distribution of interest, possesses desirable asymptotic properties, is conceptually easy to implement, and computationally attractive. In particular, we show that the test asymptotically controls size at a polynomial rate, is non-conservative, and detects local alternatives that converge to the null with the fastest possible rate. Our test is based on a data-driven bandwidth value and the critical value for the test takes this randomness into account. Monte Carlo simulations indicate that the test performs well in finite samples. In particular, the simulations show that the test controls size and may be significantly more powerful than existing alternative procedures.
Keywords: 330